Climatic Risk Atlas of European Butterflies - Irma Wynhoff (BioRisk, 2008)
The overarching aim of the atlas is to communicate the potential risks of climatic change to the future of European butterflies. The main objectives are to: (1) provide a visual aid to discussions on climate change risks and impacts on biodiversity and thus contribute to risk communication as a core element of risk assessment; (2) present crucial data on a large group of species which could help to prioritise conservation efforts in the face of climatic change; (3) reach a broader audience through the combination of new scientific results with photographs of all treated species and some straight forward information about the species and their ecology. The results of this atlas show that climate change is likely to have a profound effect on European butterflies. Ways to mitigate some of the negative impacts are to (1) maintain large populations in diverse habitats; (2) encourage mobility across the landscape; (3) reduce emissions of greenhouse gasses; (4) allow maximum time for species adaptation; (4) conduct further research on climate change and its impacts on biodiversity. The book is a result of long-term research of a large international team of scientists, working at research institutes and non-governmental organizations, many within the framework of projects funded by the European Commission.